2022
DOI: 10.3389/fphar.2022.844400
|View full text |Cite
|
Sign up to set email alerts
|

Dan-Shen-Yin Granules Prevent Hypoxia-Induced Pulmonary Hypertension via STAT3/HIF-1α/VEGF and FAK/AKT Signaling Pathways

Abstract: Traditional Chinese medicine (TCM) plays an important role in the treatment of complex diseases, especially cardiovascular diseases. However, it is hard to identify their modes of action on account of their multiple components. The present study aims to evaluate the effects of Dan-Shen-Yin (DSY) granules on hypoxia-induced pulmonary hypertension (HPH), and then to decipher the molecular mechanisms of DSY. Systematic pharmacology was employed to identify the targets of DSY on HPH. Furthermore, core genes were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The qRT-PCR results indicated that AM decreased the hypoxia-induced HIF-1α mRNA expression ( p < 0.05). AKT-1 was a major regulator of HIF-1α [ 30 ], and AM declined AKT-1 mRNA expression ( p < 0.01). As illustrated in Figure 11 , HMOX1, NOS2, NOS3, EPO, VEGFA, and SERPONE1 were all downstream molecules of the HIF-1 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The qRT-PCR results indicated that AM decreased the hypoxia-induced HIF-1α mRNA expression ( p < 0.05). AKT-1 was a major regulator of HIF-1α [ 30 ], and AM declined AKT-1 mRNA expression ( p < 0.01). As illustrated in Figure 11 , HMOX1, NOS2, NOS3, EPO, VEGFA, and SERPONE1 were all downstream molecules of the HIF-1 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Dan Shen aims to remove blood stasis and promote blood circulation, and is widely used in clinical practice for the treatment of cardiovascular diseases, and severe pulmonary bloating. 33 The whole prescription can reduce symptoms and improve pulmonary function, and lower the risk of exacerbations for patients with COPD. 9 According to the results of network pharmacology, there are 172 components in BFNSP.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics tools has been widely applied in oncology to identify genetic changes and new potential biomarkers associated with various diseases [14][15][16] . Likewise, researchers have tried to apply bioinformtics analysis in the study of PH to to elucidate the potential functions of circRNAs related to PH, mostly based on databases and animal experiments [17][18][19][20][21][22][23][24][25][26] . However, few studies have utilized clinical samples with definite diagnosis of PH, and researches for PH in COPD are even fewer.…”
Section: W I T H D R a W N S E E M A N U S C R I P T D O I F O R D E ...mentioning
confidence: 99%